Communities and Technologies 2007 2007
DOI: 10.1007/978-1-84628-905-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Introductions and Requests: Rhetorical Strategies That Elicit Response in Online Communities

Abstract: Conversation is a critical element to the success of online communities, both for the communities as a whole and the individual members. Yet conversations often fail: Forty percent of potential thread-starting messages in Usenet groups receive no response. When this happens, those who are trying to get information, support, or discussion from a group receive no benefit from their efforts. This paper presents a multi-method series of studies into community responsiveness to two rhetorical strategies: self-discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 24 publications
3
57
0
1
Order By: Relevance
“…The existing research examining the role of subject lines has generally been undertaken in the context of messages posted to online discussion forums but has yielded inconsistent results. An analysis of over 40,000 messages posted to 99 Usenet newsgroups found that inclusion of a question mark in the subject line increased the likelihood of response (Burke, Joyce, Kim, Anand, & Kraut, 2007). However, ten experiments by Callegaro Kruse, Thomas, and Nukulkij (2009) found no difference in public affairs survey completion rates between emails with customized and those with generic subject lines.…”
Section: Subject Lines and Information Gap Theorymentioning
confidence: 99%
“…The existing research examining the role of subject lines has generally been undertaken in the context of messages posted to online discussion forums but has yielded inconsistent results. An analysis of over 40,000 messages posted to 99 Usenet newsgroups found that inclusion of a question mark in the subject line increased the likelihood of response (Burke, Joyce, Kim, Anand, & Kraut, 2007). However, ten experiments by Callegaro Kruse, Thomas, and Nukulkij (2009) found no difference in public affairs survey completion rates between emails with customized and those with generic subject lines.…”
Section: Subject Lines and Information Gap Theorymentioning
confidence: 99%
“…The very first thing they crave for is a reply. Getting a reply, let alone generate a discussion is quite an achievement in itself: in a study of 40,931 messages in 99 Usenet newsgroups it was found that 43 percent of the topic starters never received a reply; similar percentages were found in other studies (Burke et al 2007). Using introductions and making requests raised the likelihood of receiving replies.…”
Section: The Consequences Of Rhetoric About Future Problemsmentioning
confidence: 77%
“…Using introductions and making requests raised the likelihood of receiving replies. This in turn has important group cohesion effects: posters who received a reply, particularly if they were newbies, were more likely to post again (Burke et al 2007).…”
Section: The Consequences Of Rhetoric About Future Problemsmentioning
confidence: 99%
“…One focus has been on the effects of introductions and requests on the level of participation of the invited user, and the success of subsequent online conversation [11]. Harper et al found a significant increase in participation from users who received a personalized introduction, and one that emphasizes social interaction [12], and Freyne et al found a similar increase when appeals to add friends and take other actions were included early in the signup process [13].…”
Section: Related Workmentioning
confidence: 99%
“…Based on Burke's findings [11] , the author believes that invitations that offer a more personal use case will be easier to understand and more immediately affecting than those that present more abstract ideals. Furthermore, the author believes that invitations which emphasize the recipient's personal safety, as well as the safety of his or her individual friends and neighbors, will be more effective in recruiting potential members.…”
Section: Hypothesismentioning
confidence: 99%